The Place of Mixed Methods in Contemporary Social Investigations - Dr. Charles Edaku (Researchparks Publishing, 2022)
This journal article titled “The place of Mixed Methods in Contemporary Social Investigations”, analyses the importance and place of mixed methods in social research. The application of mixed methods in social investigations has for some time been misunderstood by many researchers who unknowingly find themselves using mixed methods approach and designs, though wrongly. This article is one of those that adds knowledge to the existing one and the author joins the previous scholars in this area to throw light in the application of mixed methods approach and designs in research. The importance of this discussion is that, with the knowledge gained from this article students and researchers can now approach this field with deep understanding of the philosophical underpinnings, paradigms, approaches, procedures and; techniques that inform mixed methods.